(untitled) (International Journal of Studies in Nursing, 2018)
The current article describes how a Himalayan Master and Satguru, Professor and Dr. Sri Svami Purna Maharaj, uses the Vedic/Ayurvedic and other related Himalayan methodology and tradition to address the prevention of disease and promote healthy behavior among the spiritual community of students and seekers through a system developed under his guidance and supervision called the Purna Health Management System (PHMS). The article also explains some of the Vedic/Ayurvedic traditions the PHMS is based on and how they are supported by Western literature and research. Finally, it reports findings of a pilot study investigating outcomes related to self- reported physical health, mental/emotional health, and stress for those who follow the PHMS teachings and framework. The pilot study involved a cross-sectional, mixed-methods anonymous online survey of people who were practicing the PHMS teachings and implementing the system. Out of the 100 potential participants, 41 chose to complete the survey, a 41% response rate. Non-parametric Spearman’s ρ Correlation Coefficients were used to test hypotheses for relationships between frequency of implementation of the four key factors of the PHMS and the self-reported outcomes of physical health, mental/emotional health, overall stress level, and ability to manage stress. A two-tailed p < .05 was considered statistically significant. Participants of the pilot study who reported frequently implementing the PHMS also reported positive health outcomes; for example, those who reported implementing the life balance (stress management) aspect of the PHMS more frequently also reported increased physical health, increased mental/emotional health, increased ability to manage stress, and decreased overall stress. Although further research is needed, the findings of this pilot study suggest that the PHMS approach may be useful to both faith communities and health professionals wanting to promote health and prevent disease in those whom they serve.